The optimal position for insertion of orthodontic miniscrews - Bittencourt, Luiza Paiva (2011)
Purpose: Miniscrews feature several advantages over other devices used to achieve anchorage; however, using computed tomography (CT) scans to determine the appropriate areas to place these devices for all patients can be expensive. This study aimed to determine the optimal interradicular spaces for miniscrew placement in the mandible and maxilla. Methods: Using CT images from 12 adult patients, mean interradicular distance and standard deviation values were obtained at heights of 2, 5, 8 and 11 mm from the alveolar bone crest. The means were compared with mean data from the literature. Results: Considering a height of 3 mm, the most favorable mandibular interradicular distances were found between the first and second molars, first and second premolars, and finally between the canines and first premolars. The most favorable maxillary interradicular spaces were found between the canines and first premolars, between premolars, and between the second premolar and first molar. Conclusion: The safest interradicular site for miniscrew insertion in the mandible was found to be between the first and second molars, whereas in the maxilla, this site was between the canines and first premolars.